AN ANALYTICAL STUDY ON THE CONTRIBUTION OF SYMBIOTIC INSURANCE COMPANIES IN FINANCING INVESTMENT PROJECTS - THE CASE OF SALAMA INSURANCE COMPANY IN ALGERIA - Mouloud , Dr. Arzioukat (The journal of contemporary issues in business and government, 2024)
This study aims to shed light on Symbiotic insurance companies, which have become one of the main institutions within the contemporary Islamic financial system as an alternative to conventional insurance companies, on the one hand, and on the one hand, and on the one hand, to identify the reality of the practical role of Symbiotic insurance companies in financing investment projects and supporting local development by applying to Salama Insurance Company in Algeria. Investment is a major objective as much as it is interested in compensating for the damages suffered by the participants in its insurance contract and therefore has no practical contribution to financing investment in the various financing formulas adopted by the company at the theoretical level.